Enrichment effects of ionic liquid mixtures at polarized electrode interfaces monitored by potential screening dagger - Shin, Sunghwan; Greco, Francesco; Maier, Florian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2021)
The behavior of ionic liquids (ILs) at charged interfaces is pivotal for their application in supercapacitors and electrochemical cells. Recently, we demonstrated for neat ILs that potential screening at polarized electrode interfaces shows a characteristic voltage dependence, as determined in situ by X-ray photoelectron spectroscopy. Herein, we use this fingerprint-type behavior to characterize the nature of the IL/electrode interfaces for IL mixtures of [C(8)C(1)Im][Tf2N] and [C(8)C(1)Im]Cl on Au and Pt electrodes. For Au, the IL/electrode interfaces are dominated by the Cl- anions, even down to a 0.1 mol% [C(8)C(1)Im]Cl content. In contrast, [Tf2N](-) anions enrich at the IL/Pt electrode interfaces down to 10 mol% [C(8)C(1)Im][Tf2N]; only at lower concentrations does a transition to Cl- enrichment occur. These mixture studies demonstrate that even small concentrations of another IL or contamination, e.g. remaining from synthesis, can strongly influence the situation at charged IL interfaces.
CRIS-Team WoS Importer:2021-04-02

Potential Screening at Electrode/Ionic Liquid Interfaces from In Situ X-ray Photoelectron Spectroscopy - Greco, Francesco; Shin, Sunghwan; Williams, Federico J.; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter (ChemistryOpen, 2019)
A new approach to investigate potential screening at the interface of ionic liquids (ILs) and charged electrodes in a two-electrode electrochemical cell by in situ X-ray photoelectron spectroscopy has been introduced. Using identical electrodes, we deduce the potential screening at the working and the counter electrodes as a function of applied voltage from the potential change of the bulk IL, as derived from corresponding core level binding energy shifts for different IL/electrode combinations. For imidazolium-based ILs and Pt electrodes, we find a significantly larger potential screening at the anode than at the cathode, which we attribute to strong attractive interactions between the imidazolium cation and Pt. In the absence of specific ion/electrode interactions, asymmetric potential screening only occurs for ILs with different cation and anion sizes as demonstrated for an imidazolium chloride IL and Au electrodes, which we assign to the different thicknesses of the electrical double layers. Our results imply that potential screening in ILs is mainly established by a single layer of counterions at the electrode.
CRIS-Team WoS Importer:2019-10-01

Surface-Induced Changes in the Thermochromic Transformation of an Ionic Liquid Cobalt Thiocyanate Complex - May, Benjamin; Hoenle, Michael; Heller, Bettina; Greco, Francesco; Bhuin, Radha Gobinda; Steinrück, Hans-Peter; Maier, Florian (Journal of Physical Chemistry Letters, 2017)
We demonstrate that a thermodynamic. complex equilibrium within an ionic liquid film can be significantly influenced by the presence of the liquid-vacuum interface. Using surface sensitive X-ray photoelectron spectroscopy, we find that the temperature-driven transition from the blue-colored tetrahedral [Co(II) (NCS)(4)](2-) to the red-colored octahedral [Co(II) (NCS)(6)](4-) complex already occurs within the outermost nanometers at around +4 degrees C as compared with -25 degrees C in the bulk. This thermochromic transformation in the near-surface region goes along with a loss in preferential surface orientation of free [SCN](-) anions and with a pronounced decrease in the complex density; both effects are attributed to the formation of a weakly bound solvation shell around the [Co(II) (NCS)(6)](4-) anion, leading to an effective complex dilution. Our results are not only relevant for high-surface area thin film systems, such as in sensor and catalysis applications, but also shed light on the role of ionic liquid surfaces in particular and liquid surfaces in general.

Temperature-Dependent Surface Enrichment Effects in Binary Mixtures of Fluorinated and Non-Fluorinated Ionic Liquids - Heller, Bettina; Lexow, Matthias; Greco, Francesco; Shin, Sunghwan; Partl, Gabriel; Maier, Florian; Steinrück, Hans-Peter (Chemistry - A European Journal, 2020)
Using angle-resolved X-ray photoelectron spectroscopy (ARXPS), we investigate the topmost nanometers of various binary ionic liquid (IL) mixtures at different temperatures in the liquid state. The mixtures consist of ILs with the same [PF6]− anion but two different cations, namely 3-methyl-1-(3,3,4,4,4-pentafluorobutyl)imidazolium hexafluorophosphate, [PFBMIm][PF6], and 1-butyl-3-methylimidazolium hexafluorophosphate, [C4C1Im][PF6], with 10, 25, 50 and 75 mol % content of [PFBMIm][PF6]. We observe a preferential enrichment of the fluorinated chain in the topmost layer, relative to the bulk composition, which is most pronounced for the lowest content of [PFBMIm][PF6]. Upon cooling the mixtures stepwise from 95 °C until surface charging effects in XPS indicate solidification, we observe a pronounced increase in surface enrichment of the fluorinated chain with decreasing temperature in the liquid state. In contrast to the mixtures with lower [PFBMIm][PF6] contents, cooling the 75 mol % mixture additionally shows an abrupt decrease of the fluorinated chain signal before complete solidification occurs, which is assigned to partial precipitation effects.
CRIS-Team Scopus Importer:2020-02-04
Keywords: ionic liquids; mixtures; photoelectron spectroscopy; surface enrichment

The Effect of Ambient Conditions on the Potential Screening at Ionic Liquid – Electrode Interfaces - Greco, Francesco; Hemmeter, Daniel; Shin, Sunghwan; Steinrück, Hans-Peter; Maier, Florian (Journal of Ionic Liquids, 2022)
In comparison to the clean conditions of ultrahigh vacuum (UHV), we investigate the influence of ambient conditions on the potential screening (PS) at the interfaces of Au and Pt electrodes with the ionic liquids [C8C1Im][Tf2N] and [C8C1Im]Cl. Our study is based on a proof-of-principle experiment that shows that PS measurements performed by XPS yield the same results as measurements using a specific 3-electrode sample holder setup, both in UHV. Based on this, we compare PS measurements under ultraclean conditions by XPS with PS measurements with a 3-electrode setup in N2 and in air. We demonstrate that there is indeed an influence of the ambient gas atmosphere, which depends on applied voltage and combination of IL and electrode material. For Pt electrodes, there is a pronounced influence of the ambient conditions on the PS for both [C8C1Im][Tf2N] and [C8C1Im]Cl, while for Au electrodes hardly any influence is seen. We attribute the observed effects mainly to water affecting the electrical double layers at the IL/electrode interfaces. In addition, we observe that reaction products formed under faradaic conditions can lead to a contamination of the 3rd electrode (reference electrode), yielding time-dependent deviations from the true behavior.
CRIS-Team Scopus Importer:2024-12-16